2011
DOI: 10.1186/1471-2407-11-458
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus core promoter mutations G1613A and C1653T are significantly associated with hepatocellular carcinoma in genotype C HBV-infected patients

Abstract: BackgroundHepatitis B virus (HBV) is a major cause of hepatocarcinogenesis.To identify mutations relevant to hepatocellular carcinoma (HCC) development, we compared the full genome sequences of HBV from the sera of patients with and without HCC.MethodsWe compared the full genome sequences of HBV isolates from 37 HCC patients (HCC group 1) and 38 patients without HCC (non-HCC group 1). We also investigated part of the core promoter region sequences from 40 HCC patients (HCC group 2) and 68 patients without HCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…is also associated with HCC in patients infected with HBV genotype C (Mun et al, 2011). On the other hand, some studies have detected that the pre-S internal deletion mutants are unlikely to play an important role in hepatocarcinogenesis in clinical study (Tatsukawa et al, 2011). Numerous studies for mechanisms shown that deletions mutations in Pre-S in the integrated HBV DNA, may impair the secretion of HBsAg, leading to increased endoplasmic reticulum and oxidative stress in hepatocytes .…”
Section: P R E -S M U T a N T S I N H B V-r E L A T E D Hepatocarcinomentioning
confidence: 99%
“…is also associated with HCC in patients infected with HBV genotype C (Mun et al, 2011). On the other hand, some studies have detected that the pre-S internal deletion mutants are unlikely to play an important role in hepatocarcinogenesis in clinical study (Tatsukawa et al, 2011). Numerous studies for mechanisms shown that deletions mutations in Pre-S in the integrated HBV DNA, may impair the secretion of HBsAg, leading to increased endoplasmic reticulum and oxidative stress in hepatocytes .…”
Section: P R E -S M U T a N T S I N H B V-r E L A T E D Hepatocarcinomentioning
confidence: 99%
“…Mutations in basal core promoter may also involved in the development of carcinoma, the result of direct sequencing revealed that mutations including A1896, A1899 and multiple mutations T1762/A1764+A1896, T1762/A1764+A1899, and T1762/A1764+A1896+A1899 were more common in cirrhotic hepatocellular carcinoma group and non-cirrhotic hepatocellular carcinoma than chronic hepatitis B patients (Zheng et al, 2011). Moreover, a study with 37 patients and 38 controls has been performed and reported G1613A and C1653T double mutations were more prevalent in patients with HCC, thus, those mutations may serve as makers in predicting HCC development (Tatsukawa et al, 2011). Being compared with both carriers of inactive virus (25%) or patients with chronic hepatitis(35%), the frequency of T1653 mutation in box alpha, the rate among patients with HCC (70%) was significantly higher, suggesting it would lead to elevated risk of HCC (Ito et al, 2006).…”
Section: Hbv Infectionmentioning
confidence: 99%
“…Base on the inclusion criteria, only 17 case-control studies (Sakamoto et al, 2006;Tanaka et al, 2006;Shinkai et al, 2007;Wang et al, 2007;Yuan et al, 2007;Zhang et al, 2007;Fang et al, 2008;Guo et al, 2008;Jang et al, 2008;Choi et al, 2009;Ja et al, 2009;Tangkijvanich et al, 2010;Welschinger et al, 2010;Zhu et al, 2010;Cho et al, 2011;Qu et al, 2011;Tatsukawa et al, 2011) with full-text were included in this meta-analysis and 18 studies were excluded. The flow chart of study selection is summarized in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%